HYGIENIC ASPECTS OF ARCHITECTURAL AND PLANNING SOLUTIONS FOR THE CONSTRUCTION OF MENTAL HEALTH FACILITIES - Chorna, Valentyna; Makhniuk, Valentyna (Scientific Journal of Polonia University, 2023)
In order to take into account the hygienic aspects of architectural and planning solutions in the construction of new mental health facilities (general hospitals, crisis units, hospices, psychological care centers, etc.), multidisciplinary groups should be involved – architectural and planning, urban planning units, the public, medical representatives of medical institutions, relatives, patients, to take into account all the necessary in-hospital factors. To conduct a hygienic assessment of architectural and planning solutions for buildings of psychiatric health care institutions in Ukraine that were built in the eighteenth and nineteenth centuries and to provide a comparative description of the hygienic standards of psychiatric health care institutions in different countries. The study was conducted on the basis of the analysis of the DBN B.2.2-10:2022 "Health Care Facilities", scientific sources of domestic and foreign scientists. A survey was conducted among chief physicians of psychiatric hospitals in Ukraine on safe sanitary and hygienic, anti-epidemic conditions of psychiatric health care facilities. There were 55 psychiatric hospitals in Ukraine before the outbreak of full-scale war: 28.6% of them were built in the eighteenth and nineteenth centuries (from 1786 to 1945), 28.6% after the Great Patriotic War (from 1945–1991), and 42.8% during the period of Ukraine’s independence (from 1991–2013). Only 25% of psychiatric institutions have playgrounds for outdoor games equipped with tennis tables and volleyball nets (for table tennis and volleyball), 25% of hospitals have playgrounds for quiet recreation (chess, dominoes), and 12.5% have playgrounds for physical education and recreation (sports and play areas). At the same time, 41.6% of these sites are in satisfactory condition. Ukraine has adopted the State Construction Standards of Ukraine DBN B.2.2-10:2022 "Healthcare Facilities. Basic Provisions". It provides basic provisions for the design of health care facilities (buildings and structures of all types of health care facilities) during new construction and reconstruction or during major repairs in health care facilities. However, there is currently no formal sanitary legislation containing sanitary, epidemiological and hygienic requirements for the decoration, equipment and operation of health care facilities with inpatient units.